Zpresneme indikaci podávání inhibitorů kinázové aktivity EGFR - Heneberg, P (Klinicka onkologie, 2011)
Even though lung cancer incidence began to decline in the majority of industrialized countries, is still belong to cancers with one of the highest incidence and mortality rates. In the Czech Republic, epidermal growth factor receptor (EGFR) kinase activity inhibitors erlotinib and gefitinib are approved for the use as the second- and third-line treatment of non-small-cell lung cancer. In a cohort of non-small-cell lung cancer patients, erlotinib administration led to tumour regression in less than 20% of patients. However, when used in patients with EGFR-activating mutations, e.g. L858R or delE746-A750, the response rate increased to 75-82% in several parallel clinical studies. Similarly, improved response rate was reported in patients bearing amplified wild-type EGFR gene. In contrary, patients with T790M, D761Y, L747S, and T854A mutations (and some other rare abberations) were found to be resistant to treatment with small-molecule inhibitors targeting the active site of the kinase domain. These mutations do not change the EGFR affinity to gefitinib or erlotinib but the mutated receptor is able to bind ATP into its active site even in the presence of erlotinib or gefitinib, similar to a wild-type receptor without an inhibitor. Besides that, when the EGFR molecule bears both the activating (e.g. L858R) and resistance-inducing mutation (e.g. T790M), the tumour acquires resistance to both erlotinib and gefitinib treatment. Currently, research focuses on a development of new strategies that would allow treatment of patients bearing mutations inducing resistance to the small-molecule inhibitors targeted on the active site of EGFR kinase domain. Contrary to the current guidelines for Czech oncologists, identification of EGFR with any of the above mentioned resistance-inducing somatic mutations should be considered as an explicit contraindication for non-small-cell cancer treatment using small-molecule EGFR kinase activity inhibitors erlotinib or gefitinib. This should also include patients in whom a resistance-inducing mutation is detected together with any of the activating mutations or deletions.
Keywords: nádory plic; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; Carcinoma, Non-Small-Cell Lung; Quinazolines; ErbB Receptors; chinazoliny; mutace; Antineoplastic Agents; erlotinib; lidé; chemorezistence; Gefitinib; erbB receptory; Erlotinib Hydrochloride; gefitinib; protinádorové látky; Mutation; Drug Resistance, Neoplasm